PS01.020: OPTIMISTIC PATIENTS AND ITS HIDDEN PERILS: A REVIEW OF ACID REFLUX IN INDIVIDUALS POST PER-ORAL ENDOSCOPIC MYOTOMY (POEM). (14th September 2018) - Zhi Lim, Tian; Qi Leong, Wei; Chin Teo, Siok; Chen, Elya; Wei Kim, Guo; Shabbir, Asim; Yan, Bok; So, Jimmy
Abstract: Background: Per-Oral Endoscopic Myotomy (POEM) has been adopted as a treatment option for Achalasia, with similar efficacy and safety profile as laparoscopic Heller Myotomy. However, issues of acid reflux and reflux oesophagitis have often plagued these patients. We aim to evaluate the clinical outcomes and resolution of reflux disease among individuals post-POEM. Methods: A prospective review was performed for all patients who have undergone POEM from January 2014 to December 2017, with individuals analysed at the 1 year mark post-POEM. Subjective assessment of reflux was performed using self-administered questionnaires, with 24h pH impedence test and high resolution manometry providing objective correlation. Results: Forty-three individuals underwent POEM during the 4 year period. The median age was 52 years (range, 24–78), with half being males (53.5%). The individuals had a median ASA score of 2 (range, 1–3). Majority of the individuals had type II achalasia (58.1%) followed by type I (34.9%) and type III (7%). Patients presented with dysphagia (88.4%) and reflux (10%); symptomatic for a median of 36 months (range, 3–540). One-third required the use of proton pump inhibitors (PPI) for symptomatic relief, with 35% receiving prior interventions for achalasia. These patients had a median Integrated Relaxation Pressure (IRP) of 23.6 mmHg (range, 4.6–160) and a median Eckardt score of 6 (range, 1 -11). One-third developed complications such as mucosal injury (18.6%), carbon dioxide pneumoperitoneum (16.3%) and bleeding (4.7%). The median length of stay was 3 days (range, 1–6). At the 1 year mark, 86% reported improvement in dysphagia (p: 0.043 ) with 66% having reduction in ratings for their severity (p: 0.002 ) and frequency (p: 0.05 ) of reflux. The median IRP (23 vs 13 mmHg) was also significantly lower (p: 0.005 ). However, only 38.5% correlated with a normal acid exposure on the impedence test (p: 0.592). Conclusion: POEM is a promising solution in the management of achalasia given good clinical response for dysphagia and reflux. However, excessive lower oesophageal acid exposure may still be present in almost half of these patients, which may be alleviated with the use of long term use of PPI. Disclosure: All authors have declared no conflicts of interest.